Instituto Dona Escholastica Rosa (1899-1933) : a partir do ""olhar"" de Julio Conceição - Izolan , Mariela (2013)
linked to ¿LIAME¿ ¿ Information Laboratory, Archive and Memory of Education, in the search line II from the Masters Program in Education UNISANTOS. Its theme is the academic institution from the standpoint of historical and cultural heritage and as an object of study, the Institute D. Escholastica Rosa (1899-1933), located in the city of Santos/SP, as one of the first schools of vocational education in Brazil. It was conceived in 1899 and opened in 1908. The historic marking goes until 1933, a time when the space and target audience changed its initial configuration due to the new educational guidelines resulted from the Second Republic, among other factors. The objective of this paper is to analyze the design of implantation space and culture, from the ""look"" of Julio Conceição (1899-1908) in parallel to the process of urbanization of Santos and well as to identify other documents that constitute the heritage Institute. The problem lies in the state of preservation and heritage conservation, awareness about the history of the Institute and the levels and instances of heritage listing, reflecting the absence of policies related to heritage education. Given this context, this research intends to identify: What documents constitute the Institute ¿D. Escholastica Rosa¿ Historical and Cultural patrimony? As theoretical contributions the following studies are used: Le Goof (2003) on history and memory, Bencosta (2007) and Wolf (2010) on issues relating to hygiene ""drawing"" plants of schools; Julia (2001) and Faria Filho (2000) on the culture as a historical object, and Souza (1998) about the architecture school in the First Republic and its relationship to the culture of schools; Pereira (1996) on ¿Santos in the Ways of Popular Education¿ (1870-1920 ), Andrade (1995), about the urbanization process of Santos¿ (1870- 1930) and study of the legislation on legal issues relating to the preservation, conservation and the right to education equity. The methodology is as a documentary research. As procedures and techniques: We analyzed the social, political and economic development of the city of Santos in the first Republic, through a literature review. Selected documents: regulation, photos, plants of the building, reflecting the spatial and temporal phenomenon of ducation. Data were analyzed from the categories on the two dimensions studied and presented in three chapters. As result, the Institute¿s history and planning of the project were analyzed (from 1899 to 1908), as well as the school architecture and its precepts that ordered space, time and organized the specificities of vocational education in the arts and crafts from 1908 to 1933. The building belongs to the ¿Santa Casa Misericórdia de Santos¿ Brotherhood, currently administered by CEETEPS, in deep need of maintenance and is already Heritage listed, in Municipal level by CONDEPASA, and standardization by the Government of São Paulo State - CONDEPHAAT. The Federal Constitution provides the legal mechanisms that confer protection to the property, regardless the prior Heritage listing.